Brand love influence on brand equity in Kpop Industry using brand engagement as a mediating variable - Nadya Mustafa; Dina Patrisia (Universitas Negeri Padang, 2022)
This research aims to analyze the effect of brand love on brand equity in the Kpop industry with social media brand engagement as a mediating variable in fandom ATEEZ (ATINY). 200 respondents were the sample of this study. Data is processing by SmartPLS and collected from online questionnaire. The results of this study showed that (1) Brand love has a significant positive effect on social media brand engagement in fandom ATEEZ (ATINY). (2)Brand love has a significant effect on brand equity in fandom ATEEZ (ATINY). (3) Social media brand engagement has a significant effect on brand equity in fandom ATEEZ (ATINY). (4) Brand love has a significant positive effect on brand equity through social media brand engagement in fandom ATEEZ (ATINY).